2021
DOI: 10.1097/ftd.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Microsampling Devices for Routine Therapeutic Drug Monitoring—Are We There Yet?

Abstract: Background: The use of microsampling for therapeutic drug monitoring (TDM) is increasingly feasible as sensitive methods have become more accessible. There exists an increasing interest in the use of microsampling, and new microsampling devices and techniques can potentially improve patient convenience and care, among other features. This review provides an update on currently validated methods for measuring drugs pertinent to TDM, including data from clinical samples.Methods: A literature record search was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Even more, participants in this pilot study preferred this type of sampling over a conventional blood draw, but this needs to be confirmed in a larger cohort. This is in agreement with results obtained by Morgan et al, who showed that 81% of the participants preferred VAMS collection, and is in line with the preference for VAMS in the cohort studied by Verougstraete et al [23,32]. Essential to implementation, we also investigated the time it took for a sample to reach our laboratory.…”
Section: Discussionsupporting
confidence: 91%
“…Even more, participants in this pilot study preferred this type of sampling over a conventional blood draw, but this needs to be confirmed in a larger cohort. This is in agreement with results obtained by Morgan et al, who showed that 81% of the participants preferred VAMS collection, and is in line with the preference for VAMS in the cohort studied by Verougstraete et al [23,32]. Essential to implementation, we also investigated the time it took for a sample to reach our laboratory.…”
Section: Discussionsupporting
confidence: 91%
“…To decentralize the collection of blood, cutaneous capillary blood is a good alternative as it can easily be self-sampled by finger pricking using an external piercing element [ 2 ]. However, in addition to still being relatively invasive, obtaining acceptable quantities while maintaining adequate quality is often challenging [ 3 , 4 , 5 ]. Furthermore, the generated blood droplet has to be deposited manually on, for instance, the inlet of a point-of-care diagnostic test or a dried blood spot card, which often leads to volume losses or inaccurate results.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods have been applied to metabolic phenotyping experiments that have assessed outcomes of health and disease including inflammation [17], cardiometabolic diseases [21], dementia [17], and nutrition [22]; they are commonly targeted for many clinical and human physiology studies. This move towards sample miniaturisation in the space of metabolic phenotyping has led research teams to begin the evaluation of microsamples over traditional venepuncture for sample collection [23].…”
Section: Introductionmentioning
confidence: 99%